2008
DOI: 10.1177/183335830803700303
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Presentations of Victorian Aboriginal and Torres Strait Islander People

Abstract: This paper explains how routinely collected data can be used to examine the emergency department attendances of Victorian Aboriginal and Torres Strait Islander people. The data reported in the Victorian Emergency Minimum Dataset (VEMD) for the 2006/2007 financial year were analysed. The presentations of Aboriginal and Torres Strait Islander and non-Aboriginal people were compared in terms of age, gender, hospital location (metropolitan and rural) and presenting condition. Aboriginal and Torres Strait Islander … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 5 publications
(20 reference statements)
5
15
2
Order By: Relevance
“…4,5,17 The differences observed were lower than those observed here 4 and sometimes restricted to individuals living in regional areas 5 or in younger cohorts. 4,5,17 The differences observed were lower than those observed here 4 and sometimes restricted to individuals living in regional areas 5 or in younger cohorts.…”
Section: Discussioncontrasting
confidence: 67%
“…4,5,17 The differences observed were lower than those observed here 4 and sometimes restricted to individuals living in regional areas 5 or in younger cohorts. 4,5,17 The differences observed were lower than those observed here 4 and sometimes restricted to individuals living in regional areas 5 or in younger cohorts.…”
Section: Discussioncontrasting
confidence: 67%
“…In the only other Victorian study to examine their characteristics, rural ATSI had higher standardised population ED presentation rates, whereas urban ATSI had similar standardised population presentation rates to non‐ATSI. Poor ATSI status identification was a possible reason, given that no difference was found in presentation rates in urban ATSI . In an analysis of 2010–2011 Victorian Emergency Minimum Dataset (VEMD) data, no difference in presentation rates between ATSI and non‐ATSI people was found for three hospitals in Melbourne's northern suburbs, but only triage categories 4 and 5 patients were analysed .…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found that ATSI people had higher rates of population‐adjusted mental health presentations, similar rates of population‐adjusted respiratory disease presentations, and lower rates of population‐adjusted injury or poisoning presentations to metropolitan EDs compared with non‐ATSI people . Their findings are reflected in the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences also exist by remoteness. A recent study comparing emergency presentations of Victorian Indigenous people with non‐Indigenous people during the 2006/2007 financial year found that while presentation rates in metropolitan areas were similar, Indigenous people (684 per 1000) in rural areas presented 2.3 times more often than non‐Indigenous people (297 per 1000) 25. Authors state this reflects higher rates for injury and poisoning, respiratory conditions and mental disorders in these areas.…”
Section: Discussionmentioning
confidence: 99%